Respuesta :
RESOLVER:
[tex]\left[-\left(\frac{1}{4}-\frac{2}{4}\right)+\frac{6}{8}\right]+\left(\frac{6}{5}-\frac{5}{4}\right)+\frac{2}{3}[/tex]
Simplificamos
[tex]\frac{2}{4}=\frac{1}{2}[/tex]
[tex]=\left[-\left(\frac{1}{4}-\frac{1}{2}\right)+\frac{6}{8}\right]+\left(\frac{6}{5}-\frac{5}{4}\right)+\frac{2}{3}[/tex]
[tex]\frac{6}{8}=\frac{3}{4}[/tex]
[tex]=\left[-\left(\frac{1}{4}-\frac{1}{2}\right)+\frac{3}{4}\right]+\left(\frac{6}{5}-\frac{5}{4}\right)+\frac{2}{3}[/tex]
Ahora calculamos la expresión dentro del paréntesis [tex]\left[-\left(\frac{1}{4}-\frac{1}{2}\right)+\frac{3}{4}\right]:1[/tex]
[tex]=1+\left(\frac{6}{5}-\frac{5}{4}\right)+\frac{2}{3}[/tex]
[tex]\left(\frac{6}{5}-\frac{5}{4}\right):\frac{1}{20}[/tex]
[tex]=1-\frac{1}{20}+\frac{2}{3}[/tex]
[tex]\boxed{=\frac{97}{60}}[/tex]
[tex]BUENA\:\:SUERTE[/tex]